1993
DOI: 10.1038/icb.1993.25
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of resistance to Candida albicans in inbred mouse strains

Abstract: Summary Candida alhicans infections were established in eight inbred strains of mice. Using established histological criteria, only two strains (AKR and CBA/CaH) were found to exhibit severe lesions. The remainder showed only mild tissue damage. Deaths occurred in three strains: CBA/CaH, A/J and DBA/2. The last two strains lack the important complement component C5. Colony counts in the brain varied widely between strains and showed no correlation with the extent or severity of tissue destruction. However, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 10 publications
6
41
2
1
Order By: Relevance
“…Maximum linkage was found to the marker D2Mit295 (w 2 ¼ 79.4 (kidney) and 73.2 (brain); LOD ¼ 17.2 (kidney) and 15.9 (brain)), which maps to 17 cM on chromosome 2 ( Table 2). Since the gene for complement component 5 (C5/Hc) mapped less than 7 cM away from this marker 27 and had been previously implicated for its role in controlling response to candidiasis in inbred mouse strains, [28][29][30] we looked directly at this gene to determine if it was responsible for the linkage identified on this chromosome. A/J mice are deficient in C5 production, whereas B6 produce normal levels.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum linkage was found to the marker D2Mit295 (w 2 ¼ 79.4 (kidney) and 73.2 (brain); LOD ¼ 17.2 (kidney) and 15.9 (brain)), which maps to 17 cM on chromosome 2 ( Table 2). Since the gene for complement component 5 (C5/Hc) mapped less than 7 cM away from this marker 27 and had been previously implicated for its role in controlling response to candidiasis in inbred mouse strains, [28][29][30] we looked directly at this gene to determine if it was responsible for the linkage identified on this chromosome. A/J mice are deficient in C5 production, whereas B6 produce normal levels.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in inbred mouse strains have documented the critical role of the C5 complement component, whose deficiency in the form of a naturally occurring 2-bp mutation (28), causes strong susceptibility to C. albicans infection (fungal proliferation, overall survival) (10,14,16,30,53). In addition, we and others have mapped Carg loci, namely Carg1 through Carg4, that additionally regulate susceptibility to C. albicans infection in a C5-independent fashion (29,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the major effect of the C5 status on fungal replication in target organs (kidney, brain) and overall survival from C. albicans infection (10), early studies in AcB/BcA recombinant congenic mouse strains suggested that additional C5-unrelated genetic loci could also contribute to host response to C. albicans infection (10,30,31). Other studies by Ashman et al (32,33) suggested that severity of infection evaluated by type and extent of histopathologic damage in target organs is regulated by other loci (Carg1, Carg2), whose map location and identity have remained unknown.…”
mentioning
confidence: 99%
“…Over the years, the response of a number of different inbred strains to systemic candidiasis has been assessed, with fungal load and mortality being the two most commonly measured phenotypes (Table 2). 33,35,74,[106][107][108][109][110][111] For the more frequently tested strains, results between experiments are fairly consistent, despite differences in experimental conditions, such as C. albicans strain and dose used and the time of assessment of fungal load (fixed time point or at time of death). Interstrain differences are apparent with respect to susceptibility to infection with C. albicans, although correspondence between mortality and fungal burden is not always seen, suggesting the possibility of alternate genetic control for these traits.…”
Section: Studies In Inbred Mouse Strainsmentioning
confidence: 97%